A new selective fluorescent probe based on tamoxifen - Ho, L.; Thomas, E.; McLaughlin, R.; Flematti, G.; Fuller, Rebecca (Pergamon, 2016)
© 2016 Elsevier Ltd. Developing targeted validation probes that can interrogate biology is of interest for both chemists and biologists. The synthesis of suitable compounds provides a means for avoiding the costly labeling of cells with specific antibodies and the bias associated with the interpretation of biological validation experiments. The chemotherapeutic agent, tamoxifen has been routinely used in the treatment of breast cancer for decades. Once metabolized, the active form of tamoxifen (4-hydroxytamoxifen) competes with the binding of estrogens to the estrogen receptors (ER). Its selectivity in ER modulation makes it an ideal candidate for the development of materials to be used as chemical probes. Here we report the synthesis of a fluorescent BODIPY®FL conjugate of tamoxifen linked through an ethylene glycol moiety, and present proof-of-principle results in ER positive and ER negative cell lines. Optical microscopy indicates that the fluorescent probe binds selectively to tamoxifen sensitive breast cancer cell lines. The compound showed no affinity for the tamoxifen resistant breast cancer lines. The specificity of the new compound make it a valuable addition to the chemical probe tool kit for estrogen receptors.